Facile and Scalable Preparation of Fluorescent Carbon Dots for Multifunctional Applications - Wang, Dan; Wang, Zhiyong; Zhan, Qiuqiang; Pu, Yuan; Wang, Jie-Xin; Foster, Neil R.; Dai, Liming (Engineering (Beijing, China), 2017)
The synthesis of fluorescent nanomaterials has received considerable attention due to the great potential of these materials for a wide range of applications, from chemical sensing through bioimaging to optoelectron- ics. Herein, we report a facile and scalable approach to prepare fluorescent carbon dots （FCDs） via a one-pot reaction of citric acid with ethylenediamine at 150 ℃ under ambient air pressure. The resultant FCDs pos- sess an optical bandgap of 3.4 eV and exhibit strong excitation-wavelength-independent blue emission （λEm = 450 nm） under either one- or two-photon excitation. Owing to their low cytotoxicity and long fluorescence lifetime, these FCDs were successfully used as internalized fluorescent probes in human cancer cell lines （HeLa cells） for two-photon excited imaging of cells by fluorescence lifetime imaging microscopy with a high-contrast resolution. They were also homogenously mixed with commercial inks and used to draw fluo- rescent patterns on normal papers and on many other substrates （e.g., certain flexible plastic films, textiles, and clothes）. Thus, these nanomaterials are promising for use in solid-state fluorescent sensing, security labeling, and wearable optoelectronics.